2020
DOI: 10.1101/2020.08.27.270819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elucidation of remdesivir cytotoxicity pathways through genome-wide CRISPR-Cas9 screening and transcriptomics

Abstract: The adenosine analogue remdesivir has emerged as a frontline antiviral treatment for SARS-CoV-2, with preliminary evidence that it reduces the duration and severity of illness1. Prior clinical studies have identified adverse events1,2, and remdesivir has been shown to inhibit mitochondrial RNA polymerase in biochemical experiments7, yet little is known about the specific genetic pathways involved in cellular remdesivir metabolism and cytotoxicity. Through genome-wide CRISPR-Cas9 screening and RNA sequencing, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Additional biochemical assays showed the active triphosphate metabolite GS-443902 was a poor substrate for mitochondrial DNA and RNA polymerases, even when tested at supraphysiological concentrations of 50 and 500 μM, respectively. A recent paper reported the effects of RDV on cellular toxicity through a transcriptomic analysis, and reported effects of RDV on mitochondrial function ( 26 ). However, it is not clear whether the results were due to specific mitochondrial toxicity or general cellular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Additional biochemical assays showed the active triphosphate metabolite GS-443902 was a poor substrate for mitochondrial DNA and RNA polymerases, even when tested at supraphysiological concentrations of 50 and 500 μM, respectively. A recent paper reported the effects of RDV on cellular toxicity through a transcriptomic analysis, and reported effects of RDV on mitochondrial function ( 26 ). However, it is not clear whether the results were due to specific mitochondrial toxicity or general cellular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research reported that remdesivir was superior to placebo in shortening the time to recovery of hospitalized COVID-19 patients [96]. Whereas, in vitro experiments showed that Remdesivir and its metabolites were cytotoxic and mitochondrial toxic to a variety of cells, especially hepatocytes [97]. In a trial comparing remdesivir treatment for either 5 or 10 days, severe but not immediately life-threatening ALT/AST elevations were reported in 4-6% of patients and life-threatening AST/ALT elevations in 2-3% of patients [98].…”
Section: Drug-induced Liver Injurymentioning
confidence: 99%
“…Two recent studies have utilized this method in both Vero cells and hepatoma cells and identified host factors ACE2, the protease Cathepsin L, and TMEM106B to play a crucial role in viral infection ( Wang et al., 2020b ; Wei et al., 2020 ). Another study utilized genome-wide CRISPR screens to elucidate the cytotoxicity pathways of remdesivir, a drug that is now commonly administered to SARS-CoV-2 patients ( Akinci et al., 2020 ). These insights gathered from classical cell lines, await confirmation in more physiologically relevant systems, such as organoids.…”
Section: The Crispr Search For Host Factors Of Sars-cov-2 Entrymentioning
confidence: 99%